Molecular Recognition: How Photosynthesis Anchors the Mobile Antenna. (May 2019) - Allen, John F.; Nield, Jon; Krauß, Norbert
Abstract : True to its name, light-harvesting complex II (LHC II) harvests light energy for photosystem II (PS II). However, LHC II can stray, harvesting light energy for photosystem I (PS I) instead. Cryo-electron microscopy (cryo-EM) now shows how this mobile antenna becomes so attached to its new partner.